Mathematical programming for the computation of multi-market equilibria: an attempt in modelling the French markets of cereals and livestock feeds - Jayet P.-A. (Comprehensive economic and spatial bio-energy modelling, 2002)
Sectorial models based on linear programming are frequently developed for the agricultural production and animal feed industry sectors. The analysis proposes the interaction of two models to represent each of these sectors, given the fact that one supplies what the other demands. This multi-market modelling is used to determine equilibrium prices and quantities. Emphasis is placed on the operational character of the process while several of the limitations inherent in the approach are pointed out.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)